Identification of Variants in Genes Associated with Single-gene Inflammatory Bowel Disease by Whole-exome Sequencing. Issue 10 (October 2016) - Ashton, James J.; Andreoletti, Gaia; Coelho, Tracy; Haggarty, Rachel; Batra, Akshay; Afzal, Nadeem A.; Beattie, R. Mark; Ennis, Sarah
Abstract : Background: Most cases of inflammatory bowel disease (IBD) are caused by complex host–environment interaction. There are a number of conditions associated with a single-gene mutation, most cases are very early onset (aged < 6 yr), present with a unique form of disease and often have atypical features. Methods: Whole-exome data for 147 pediatric patients with IBD were interrogated for a panel of 51 genes associated with monogenic IBD. Observed variation was categorized according to the American College of Medical Genetics (ACMG) guidelines to identify rare, novel, and known variants that might contribute to IBD. Results: Five hundred seventy-four variants were identified across 51 genes. These were categorized in line with ACMG guidance to remove benign variants and to identify "pathogenic" and "likely pathogenic" variants. In 6 patients, we observed 6 pathogenic variants of which CYBA (c.287+2T>C), COL7A1 (c.6501+1G>C), LIG4 (p.R814X), and XIAP (p.T470S) were known causative mutations, and FERMT1 (p.R271Q) and SKIV2L (c.354+5G>A) were novel. In the 3 patients with XIAP, SKIV2L, and FERMT1 variants, individuals' disease features resembled the monogenic phenotype. This was despite apparent heterozygous carriage of pathogenic variation for the latter 2 genes. The XIAP variant was observed in a hemizygous male. Conclusions: Whole-exome sequencing allows for identification of known and de novo potentially causative mutations in genes associated with monogenic IBD. Although these are rare conditions, it is vital to identify causative mutations early to improve prognosis. We postulate that in a subset of IBD, heterozygous mutations (in genes believed to manifest IBD through autosomal recessive inheritance) may contribute to clinical presentation. Abstract : Supplemental Digital Content is Available in the Text.Article first published online 17 August 2016.